PENGARUH PELATIHAN KERJA, MOTIVASI KERJA DAN ETOS KERJA TERHADAP KINERJA SALES PT. ALFA SCORPH MEDAN - Pudyastuti, Esty (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2022)
This research is a quantitative research which aims to determine whether job training, work motivation and work ethic influence the sales performance of PT. Alfa Scorpii Medan. The population used in this research is state-owned companies listed on the Indonesia Stock Exchange (BEI) in 2013-2017. The number of samples obtained using several criteria was 100 data. This research uses the Logistic Regression Analysis method with the help of the E-Views (Statistical Product and Service Solution) data processing program version 10. The results of this research show that the fixed asset intensity variable has no effect on the decision to revaluate fixed assets, the liquidity variable and the cash flow from variable. operation has a significant negative effect on fixed asset revaluation decisions. Meanwhile, the leverage and firm size variables have a significant positive effect on fixed asset revaluation decisions